An efficient deep learning approach to detect citrus leaves disease - Emon, Shaharear Hossain; Islam, Iftea Khairul; Nahin, Tasfia Jahan; Ahmed, Ahnaf Mahdin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.